PENINGKATAN KEMAMPUAN GURU-GURU SEKOLAH MENENGAH KEJURUAN (SMK) DALAM MERENCANAKAN PEMBELAJARAN AKUNTANSI - La Ode Turi; Murniati Murniati (LP2M STP Mataram, 2022)
The main problem experienced by accounting teachers in preparing for learning in SMK is their lack of competence to design a lesson plan (RPP). It is mainly caused by the teachers’ competencies which are not yet optimal for designing (a) Kurikulum Tingkat Satuan Pendidikan (KTSP), (b) Syllabus and RPP, (c) learning materials, (d) learning media, (e) learning scenario and (f) evaluation and its follow-up. Therefore, the teachers’ competencies in preparing accounting lesson plans need to be improved so that their output is aligned with the demands of the curriculum. To solve this issue, community service was conducted in the forms of a workshop and intensive mentoring. Through this community service, the teachers’ professionalism in preparing accounting lesson plans was successfully improved. The teachers’ improvement can be seen from the results of the pretest and post-test tested before and after the training/workshop for the accounting teachers of SMKN 1 Kendari. The implementation of this community service results in the improvement of the teachers’ competencies in preparing an accounting lesson plan and their positive responses make this training more meaningful. After this community service, it is hoped that the accounting teachers in SMK can design and improve learning so the students’ competencies may be improved accordingly.